Johann Sebastian Bach - Bitter, Karl Hermann 1813-1885 (Dresden Baensch, 1880)
In 1865 Karl Hermann Bitter published a two-volume Bach biography. The biography contains some documents from Bach's time that hadn't been published before, presented with a wealth of historical inferences and personal reflections. An abridged English translation of the biography appeared in 1873. Shortly after becoming Prussian minister of finance in 1879, Bitter published an enlarged reworking in four volumes of the biography.
Keywords: Bach, Johann Sebastian -- 1685-1750; 18th Century (1701-1800); Biography; Music history; Germany